Literature Review: Acute Respiratory Distress Syndrome (ARDS) - Oneiya, Baiq Aisha Aryuni; Ramadhita, Nova Izza Salsa; Makbul, Ini Hidayat; Mutia, Baiq Marceliya Anjani; Fidelia, Puspa Zalika; Amanullah, Mohammad Sany Rosafi; Rivlan, Muhammad Zaidan Fadlurrohman; Fathana, Prima Belia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acute Respiratory Distress Syndrome (ARDS) is a clinically and biologically heterogeneous disease with a wide range of etiologies and manifestations. ARDS contributes significantly to high morbidity, mortality, and treatment costs associated with lung disease incidence. This study aims to evaluate the clinical characteristics, diagnostic strategies, and effective management approaches in ARDS treatment to enhance clinical guidelines in intensive care practice. This study employs a literature review method by collecting relevant articles from scientific databases, including PubMed, ScienceDirect, Cochrane Library, Google Scholar, and Proquest. Selected articles are full-text publications in Indonesian and English, published between 2010 and 2023. A total of 15 articles that met the selection criteria were analyzed in this study. ARDS is a serious medical condition with a still concerning prognosis. Optimal management approaches, especially through the use of protective ventilation and prone positioning, have been shown to benefit patients. However, personalized therapy based on biomarkers and further molecular research is needed to further reduce mortality.